Echocardiographic diagnosis of the different phenotypes of hypertrophic cardiomyopathy. Issue 1 (December 2015) - Parato, Vito; Antoncecchi, Valeria; Sozzi, Fabiola; Marazia, Stefania; Zito, Annapaola; Maiello, Maria; Palmiero, Pasquale
Abstract Hypertrophic Cardiomyopathy (HCM) is an inherited cardiovascular disorder of great genetic heterogeneity and has a prevalence of 0.1 – 0.2 % in the general population. Several hundred mutations in more than 27 genes, most of which encode sarcomeric structures, are associated with the HCM phenotype. Then, HCM is an extremely heterogeneous disease and several phenotypes have been described over the years. Originally only two phenotypes were considered, a more common, obstructive type (HOCM, 70 %) and a less common, non-obstructive type (HNCM, 30 %) (Maron BJ, et al. Am J Cardiol 48:418 –28, 1981). Wigle et al. (Circ 92:1680–92, 1995) considered three types of functional phenotypes: subaortic obstruction, midventricular obstruction and cavity obliteration. A leader american working group suggested that HCM should be defined genetically and not morphologically (Maron BJ, et al. Circ 113:1807–16, 2006). The European Society of Cardiology Working Group on Myocardial and Pericardial Diseases recommended otherwise a morphological classification (Elliott P, et al. Eur Heart J 29:270–6, 2008). Echocardiography is still the principal tool for the diagnosis, prognosis and clinical management of HCM. It is well known that the echocardiographic picture may have a clinical and prognostic impact. For this reason, in this article, we summarize the state of the art regarding the echocardiographic pattern of the HCM phenotypes and its impact on clinical course and prognosis.